2021
DOI: 10.1063/5.0065538
|View full text |Cite
|
Sign up to set email alerts
|

A review of many-body dissipative particle dynamics (MDPD): Theoretical models and its applications

Abstract: Many-body dissipative particle dynamics (MDPD) is a novel coarse-grained numerical method that originated from dissipative particle dynamics. In the MDPD system, a density-dependent repulsive interaction and an attractive term are introduced into a conservative force, enabling the formation of vapor–liquid coexistence. In the last two decades, the MDPD is becoming a powerful tool to study various interfacial problems at mesoscale due to its Lagrangian and adaptive features. In the present paper, we review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 203 publications
0
32
0
Order By: Relevance
“…62−64 The mDPD model can reproduce the compressibility of real liquid fluids as a function of pressure by considering the many-body interactions 55,65−68 and has been applied for qualitative studies of surface tension, 69 contact angle characterization, 70,71 multiphase flow in microchannels, 72−74 droplets impact on surfaces, 75−78 and nanocapillaries. 79 A recent review of mDPD on its theories and applications is reported in Zhao et al 80 Despite the many attractive features of mDPD, historically it has been a challenge for mDPD to accurately simulate the static and dynamic properties of real fluids simultaneously. A modified mDPD model was recently developed to enable accurate simulations of real-fluid compressibility (in a wide range of confinement pressure), surface tension, diffusivity, and viscosity simultaneously.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…62−64 The mDPD model can reproduce the compressibility of real liquid fluids as a function of pressure by considering the many-body interactions 55,65−68 and has been applied for qualitative studies of surface tension, 69 contact angle characterization, 70,71 multiphase flow in microchannels, 72−74 droplets impact on surfaces, 75−78 and nanocapillaries. 79 A recent review of mDPD on its theories and applications is reported in Zhao et al 80 Despite the many attractive features of mDPD, historically it has been a challenge for mDPD to accurately simulate the static and dynamic properties of real fluids simultaneously. A modified mDPD model was recently developed to enable accurate simulations of real-fluid compressibility (in a wide range of confinement pressure), surface tension, diffusivity, and viscosity simultaneously.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In DPD, simulations of multiphase fluid dynamics (including fluid–fluid and fluid–solid interactions) are made possible by several multiphase-enabled DPD models. Among the DPD model variants, the many-body DPD (mDPD) model is a prominent candidate for mesoscopic simulations of fluid flow in nanoporous materials. The mDPD model can reproduce the compressibility of real liquid fluids as a function of pressure by considering the many-body interactions , and has been applied for qualitative studies of surface tension, contact angle characterization, , multiphase flow in microchannels, droplets impact on surfaces, and nanocapillaries . A recent review of mDPD on its theories and applications is reported in Zhao et al…”
Section: Introductionmentioning
confidence: 99%
“…These are the representative values for a multiphase flow in an MDPD system. [52][53][54] The subscripts w and i denote the working fluid in the channel and the infused liquid in the groove, respectively. In addition, the subscripts l and s denote the liquid (working fluid and lubricant fluid) and the solid wall, respectively.…”
Section: Mdpd Parametersmentioning
confidence: 99%
“…In DPD, simulations of multiphase/component flow are enabled by several model variants, , ,,, among which the many-body DPD (mDPD) model is prominent for mesoscopic simulations of multicomponent flow in nanoporous media. , The mDPD model can predict the compressibility of real liquids as a function of pressure by considering the many-body interactions ,,,, and has been applied in the studies of surface tension, contact angle, , multiphase flow in microchannels, droplets on surfaces, ,,, and nanocapillaries . A review of mDPD was recently reported by Zhao et al…”
Section: Introductionmentioning
confidence: 99%
“…79,80 The mDPD model can predict the compressibility of real liquids as a function of pressure by considering the manybody interactions 51,68,69,71,76 and has been applied in the studies of surface tension, 15 contact angle, 33,83 multiphase flow in microchannels, 4−6 droplets on surfaces, 10,30,73,74 and nanocapillaries. 8 A review of mDPD was recently reported by Zhao et al 88 Despite the many proven capabilities of mDPD, it has been a challenge for mDPD to accurately simulate the static and dynamic properties of real fluids at the same time. A modified mDPD model has recently been developed for accurate simulations of real-fluid compressibility in wide ranges of confinement pressure, surface tension, diffusivity, and viscosity simultaneously.…”
Section: ■ Introductionmentioning
confidence: 99%